The Terrorism Detention Center: A Philosophical Analysis Through Architecture, Technology, and Spatiality - Castillo Gómez, Francisco José (2025)
This research aims to analyze the Terrorism Confinement Center (CECOT) in El Salvador from the perspectives of philosophy, technology, space and architecture. In the first instance, some relevant notions will be explored in the understanding of the prison sentence in the course of history in the West. Secondly, the relationship between architecture and the conceptualization of both the prison and the prisoners will be analyzed. Likewise, some elements of reflection on the relationship between spatiality and corporeality in the prison context will be presented.